Proceedings of the First ACM Workshop on Secure Execution of Untrusted Code 2009
DOI: 10.1145/1655077.1655082
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-enforced fine-grained isolation of untrusted code

Abstract: We present a novel combination of hardware (architecture) and software (compiler) techniques to support the safe execution of untrusted code. While other efforts focus on isolating processes, our approach isolates code and data at a function (as in, C function) level, to enable fine-grained protection within a process as needed for downloaded plugins, libraries, and modifications of open-source projects. Our solution also enforces timing restrictions to detect denial of service from untrusted code, and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Three CAM accelerated tables maintain container context. The Container Identification Table lists [10][11][12][13][14][15][16][17][18][19][20] for critical operation speedup. The loading of the container permission state is accelerated by a dedicated permission cache, which helps reduce the fetch delays and limits the memory bus load.…”
Section: Architecture Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Three CAM accelerated tables maintain container context. The Container Identification Table lists [10][11][12][13][14][15][16][17][18][19][20] for critical operation speedup. The loading of the container permission state is accelerated by a dedicated permission cache, which helps reduce the fetch delays and limits the memory bus load.…”
Section: Architecture Overviewmentioning
confidence: 99%
“…Recent work on fast CAMs for range-checking has shown that the speed of the rangechecking is on par with regular CAM lookups, which can be achieved in a single cycle [22]. Further details of our architecture design and optimization techniques are addressed in a separate paper [14].…”
Section: Architecture Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prior work introduced hardware containers [3], [4] for fine-grained isolation of code and data that targets code written with a hierarchical control flow, which is normal in imperative, procedural, and object-oriented languages. Containers isolate code at the granularity of functions as a natural boundary for structured components and programs.…”
Section: Introductionmentioning
confidence: 99%